2012
DOI: 10.1111/j.1461-0248.2012.01749.x
|View full text |Cite
|
Sign up to set email alerts
|

Rapid genetic change underpins antagonistic coevolution in a natural host‐pathogen metapopulation

Abstract: Antagonistic coevolution is a critical force driving the evolution of diversity, yet the selective processes underpinning reciprocal adaptive changes in nature are not well understood. Local adaptation studies demonstrate partner impacts on fitness and adaptive change, but do not directly expose genetic processes predicted by theory. Specifically, we have little knowledge of the relative importance of fluctuating selection vs. arms-race dynamics in maintaining polymorphism in natural systems where metapopulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
217
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 203 publications
(223 citation statements)
references
References 59 publications
(141 reference statements)
4
217
1
1
Order By: Relevance
“…Coevolutionary dynamics between hosts and parasites is increasingly investigated using experimental evolution (15) and more specifically time-shift assays (16)(17)(18), in which hosts or parasites from a given time point are compared with their counterparts from the past or future, enabling the examination of putative reciprocal adaptations (19,20). Some of the prime experimental models are bacteria and their lytic phages, which exhibit rapid evolution and are amenable to time-shift tests.…”
mentioning
confidence: 99%
“…Coevolutionary dynamics between hosts and parasites is increasingly investigated using experimental evolution (15) and more specifically time-shift assays (16)(17)(18), in which hosts or parasites from a given time point are compared with their counterparts from the past or future, enabling the examination of putative reciprocal adaptations (19,20). Some of the prime experimental models are bacteria and their lytic phages, which exhibit rapid evolution and are amenable to time-shift tests.…”
mentioning
confidence: 99%
“…Thus, we speculate that barrier defences early in the infection process may play a crucial role in shaping the distribution of genetic variation for resistance in a given system. Barrier defences are also at the heart of gene-for-gene models in plant-pathogen interactions, which have been suggested to have an important role in Red Queenlike coevolutionary dynamics (Frank, 1993;Thrall et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…B 281: 20132567 predicted to covary positively with resistance, and negatively with tolerance as the cost of resistance decreases; or (ii) virulence is predicted to covary negatively with resistance, and positively with tolerance as the cost of tolerance decreases. According to experimental studies focusing on pathogen virulence, considerable spatial variation is observed in this three-component interaction, as well as in the strength of local coevolutionary dynamics [59]. Hence, demonstrating significant transmission across generations for tolerance and resistance is an important prerequisite for understanding coevolution between virulence, resistance and tolerance.…”
Section: Evolutionary Implications and Conclusionmentioning
confidence: 99%